Clinically useful screen for borderline personality disorder in psychiatric out-patients. (February 2017) - Zimmerman, Mark; Multach, Matthew D.; Dalrymple, Kristy; Chelminski, Iwona
Summary: A total of 3674 psychiatric out-patients were evaluated with a semi-structured diagnostic interview for DSM-IV borderline personality disorder (BPD). The affective instability criterion had a sensitivity of 92.8%, higher than the sensitivities of the other eight BPD criteria. The negative predictive value of the affective instability criterion was 99%. We recommend that clinicians screen for BPD in the same way that they screen for other psychiatric disorders: by enquiring about a single feature of the disorder (i.e. affective instability), the presence of which identifies most patients with the disorder and the absence of which rules out the disorder.